Saṭwat al-Naṣ: Khiṭāb al-Azhar wa Azmat al-Ḥukm (By Basma Abdel Aziz) (American Journal of Islam and Society, 2021)
The academic literature on the ulama and the Arab uprisings has been strangely silent about al-Azhar and its shaykh Dr. Ahmad al-Tayyeb, with very few exceptions.  Though largely neglected (mostly because it is written in Arabic), Saṭwat al-Naṣ: Khiṭāb al-Azhar wa Azmat al-Ḥukm (The Power of the Text: Al-Azhar’s Discourse and the Rule Crisis) provides a valuable contribution to the literature in that regard, on the level of data, methods, and analysis.